Impact of COVID-19 lockdown on pain and physical function in patients with advanced hip and knee osteoarthritis - P., Amaresh C.; V., Puttakemparaju K. (International Journal of Research in Orthopaedics, 2025)
Background: Osteoarthritis is the most common degenerative disease of joints that impairs quality of life and leads to disability. Hence, this study aims to assess the impact of lockdown on pain and physical function in patients with advanced knee and hip Osteoarthritis. Methods: A total of 86 patients between the age of 35 to 80 years with advanced hip and knee osteoarthritis were considered for the study during the second wave of COVID 19 lockdown. The subjects were contacted over phone call and a questionnaire was put forward after obtaining their consent. Subsequently the interviews were repeated in the fourth week and at the end of lockdown. The observers were blinded for the previous results. Visual analogue scale (VAS), Tegner activity scale (TAS), McMaster Universities Osteoarthritis questionnaire (WOMAC) scores of the patients were obtained. Comparative analysis was made based on these parameters at pre, during and after lockdown period. Results: Positive, strong to very strong and significant Pearson’s correlation was seen between VAS and WOMAC scores at all the time intervals in both the groups (knee and hip) and overall. Negative, moderate to strong and significant correlation was seen between VAS and TAS scores. A weak, moderate and significant correlation was seen between WOMAC and TAS scores. Conclusions: Our study depicts that the COVID-19 lockdown had a significant negative impact on patients with end-stage hip and knee osteoarthritis resulting in increased pain and deteriorating joint function with reduced quality of life. We suggest that virtual education in the form of web physiotherapy, online knee and hip schools and holistic self-management strategies are vital to improve pain and physical function.